Known Allergen Structures Predict Schistosoma mansoni IgE-Binding Antigens in Human Infection - Farnell, Edward J.; Tyagi, Nidhi; Ryan, Stephanie; Chalmers, Iain W.; Pinot de Moira, Angela; Jones, Frances M.; Wawrzyniak, Jakub; Fitzsimmons, Colin M.; Tukahebwa, Edridah M.; Furnham, Nicholas; Maizels, Rick M.; Dunne, David W. (Frontiers in Immunology, 2015)
The IgE response has been associated with both allergic reactions and immunity to metazoan parasites. Recently we hypothesized that all environmental allergens bear structural homology to IgE binding antigens from metazoan parasites and that this homology defines the relatively small number of protein families containing allergenic targets. In this study known allergen structures (Pfam domains) from major environmental allergen families were used to predict allergen-like (SmProfilin, SmVAL6, SmLipocalin, SmHSP20, SmTPI, SmThioredoxin, SmSOD, SmCyclophilin, SmPGK) and non-allergen-like (SmDLC, SmAldolase SmAK, SmUbiquitin, Sm14-3-3) proteins in Schistosoma mansoni. Recombinant antigens were produced in Escherichia coli and IgG1, IgG4 and IgE responses against them measured in a cohort of people (n=222) infected with S. mansoni. All allergen-like antigens were targeted by IgE responses in infected subjects, whilst IgE responses to the non-allergen like antigens, SmAK, SmUbiquitin and Sm14-3-3 were essentially absent being of both low prevalence and magnitude. Two new IgE binding Pfam domain families, not previously described in allergen family databases, were also found, with prevalent IgE responses against SmDLC (PF01221) and SmAldolase (PF00274). Finally it was demonstrated that immunoregulatory serological processes typically associated with allergens also occurred in responses to allergen-like proteins in S. mansoni infections, including the production of IgG4 in people responding with IgE and the down regulation of IgE in response to increased antigen exposure from S. mansoni eggs. This study establishes that structures of known allergens can be used to predict IgE responses against homologous parasite allergen-like molecules (parallergens) and that serological responses with IgE/IgG4 to parallergens mirror those seen against allergens, supporting our hypothesis that allergenicity is rooted in expression of certain protein domain families in metazoan parasites.